Follicular T Cells from smB− Common Variable Immunodeficiency Patients Are Skewed Toward a Th1 Phenotype - Cunill, Vanesa; Clemente, Antonio; Lanio, Nallibe; Barceló, Carla; Andreu, Valero; Pons, Jaume; Ferrer, Joana M. (Frontiers in Immunology, 2017)
Germinal center follicular T helper (GCTfh) cells are essential players in the differentiation of B cells. Circulating follicular T helper (cTfh) cells share phenotypic and functional properties with GCTfh cells. Distinct subpopulations of cTfh with different helper capabilities towards B cells can be identified: cTfh1 (CXCR3+CCR6-), cTfh2 (CXCR3-CCR6-) and cTfh17 (CXCR3-CCR6+). Alterations in cTfh function and/or distribution have been associated with autoimmunity, infectious diseases and more recently with several monogenic immunodeficiencies. Common variable immunodeficiency disease (CVID) is the commonest symptomatic primary immunodeficiency (PID) with a genetic cause identified in only 2-10% of patients. Although a heterogeneous disease, most patients show a characteristic defective B cell differentiation into memory B cells or antibody secreting cells. We investigated if alterations in CVID cTfh cells frequency or distribution into cTfh1, cTfh2, cTfh17 subpopulations and regulatory follicular T (Tfr) cells could be related to defects in CVID B cells. We found increased percentages of cTfh exhibiting higher PD-1 expression and altered subpopulations distribution in smB- CVID patients. In contrast to smB+ patients and controls, cTfh from smB- CVID patients show increased cTfh1 and decreased cTfh17 subpopulation percentages and increased CXCR3+CCR6+ cTfh, a population analogous to the recently described pathogenic Th17.1. Moreover, Tfr cells are remarkably decreased only in smB- CVID patients. In conclusion, increased cTfh17.1 and cTfh1/cTfh17 ratio in CVID patients could influence B cell fate in smB- CVID patients, with a more compromised B cell compartment, and the decrease in Tfr cells may lead to high risk of autoimmune conditions in CVID patients.